Aerodynamic and Structural Integrated Optimization Design of Horizontal-Axis Wind Turbine Blades - Jie Zhu (Energies, 2016)
A procedure based on MATLAB combined with ANSYS is presented and utilized for the aerodynamic and structural integrated optimization design of Horizontal-Axis Wind Turbine (HAWT) blades. Three modules are used for this purpose: an aerodynamic analysis module using the Blade Element Momentum (BEM) theory, a structural analysis module employing the Finite Element Method (FEM) and a multi-objective optimization module utilizing the non-dominated sorting genetic algorithm. The former two provide a sufficiently accurate solution of the aerodynamic and structural performances of the blade; the latter handles the design variables of the optimization problem, namely, the main geometrical shape and structural parameters of the blade, and promotes function optimization. The scope of the procedure is to achieve the best trade-off performances between the maximum Annual Energy Production (AEP) and the minimum blade mass under various design requirements. To prove the efficiency and reliability of the procedure, a commercial 1.5 megawatt (MW) HAWT blade is used as a case study. Compared with the original scheme, the optimization results show great improvements for the overall performance of the blade.